Paul and the competing mission in Corinth - Goulder, Michael Douglas (Library of Pauline studies, 2001)
Most of Paul's letters were written in the context of conflict with trouble-making opponents, but scholars disagree as to who those opponents were. Years ago F. C. Baur suggested that two competing missions-one headed by Paul, the other by James, Peter, and John-sent out a series of emissaries to win converts to the Christian faith. In Paul and the Competing Mission in Corinth Michael Goulder has examined Paul's conflict with the counter-missionaries, especially as reflected in the Corinthian Letters, and has put a new spin on Baur's theory. In this book, which is the culmination of decades of work, Goulder has painted a simple and convincing picture of the relationship between the mission of Paul and that of the counter-missionaries, whom he identifies as those evangelists sent by the "pillars" in Jerusalem. Goulder presents carefully assembled evidence in order to advance our picture of the early church and Paul's place in it. His two-missions hypothesis amounts to a comprehensive theory of the origins of Christianity and the New Testament.